Phytochemical constituents, chemotaxonomic significance and anti-arthritic effect of Eucommia ulmoides Oliver staminate flowers - Rui Li; Lanlan Nie; Qing Wang; Danwei Ouyang; Lei Zhang; Ying Yuan; Yanlong Hong; Jianying Wang; Xiao Hu (Natural Product Research, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Late Early-Cretaceous Magma Mixing in the Langqi Island, Fujian Province, China: Evidences from Petrology, Geochemistry and Zircon Geochronology - Liangliang Huang; Liyuan Wang; Hong-Rui Fan; Musen Lin; Wenhui Zhang (Journal of Earth Science, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Differential anthocyanin accumulation in radish taproot: importance of RsMYB1 gene structure - Biao Lai; Yuanyi Cheng; Hong Liu; Qiuxia Wang; Qi Wang; Chunlan Wang; Rui Su; Fabo Chen; Huicong Wang; Lina Du (Plant Cell Reports, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Characterization and fine mapping of Arabidopsis RLL3, a locus required for DNA demethylation pathway - Wei Miao; Jie Dai; Yumei La; Chong Lu; Jianzhen Zhang; Xinyue Hong; Shaoxia Zhou; Qianqian Wang; Xiangyu Wang; Qi Rui; Feng Tan; Honggui La (Molecular Genetics and Genomics, 2020)